Efeito de óleos essenciais de gengibre e acilaçúcares sintéticos sobre artrópodes-praga - Gomes, Anni Cristini Silvestri (2016)
The data of FAO (2015) indicate that the percentage of losses in agricultural production caused by arthropod pests is 15.6%. This percentage is fairly high when it is about foods that are produced and lost. However, the demand for products arising in a natural way that present efficiency in pest control has been widely researched. The objective was to chemically characterize the essential oils of ginger (fresh and dried), evaluate the acaricide activity against the twospotted spider mite (Tetranychus urticae) by resistance and oviposition tests; synthesize molecules of acylsugar, characterize them physicochemically and conduct biological testing efficiency of the same against the two-spotted spider mite and whitefly. The essential oils were obtained by hydrodistillation technique using the modified Clevenger apparatus. The synthesis of acylsugar occurred by a reflux system in which the molecules of glucose and sucrose were acetylated. The major constituents of the both essential oils were the same (geranial, neral, 1,8-cineole) just varying in proportions, but the α-zingiberene has been found only in fresh essential oil. In repellency activity of the twospotted spider mite was found that the most effective concentrations were 250 and 500 µL L -1 (fresh ginger) and 500 and 750 µL L -1 (dry ginger); the repellency effect was given only in the first 20 minutes. It was found efficiency of mortality of T. urtiace, being statistically all equals treatments (p≤0.05), by presenting a mortality of approximately 80%. The oviposition was affected by both essential oils, and the highest tested concentrations of both oils presented more efficiently. Both acylsugar obtained were sucrose octa-acetate and glucose penta-acetate, characterized by infrared spectroscopy and 1 H and 13 C-NMR. It was verified in mite repellency test, a linear fit between the concentration and movement of the two-spotted spider mite. Both substances obtained showed a delay in onset of arthropod egg, causing a mortality of approximately 95% on the 1st instar larvae of mites and confirmed in adults. In the biological tests with Bemisia tabaci biotype B, there was an effect on eggs and nymphs, which also occurred in a bad training in small change instar nymph to fly. Both essential oils of ginger as the synthesized acylsugar showed potential in the control of pest arthropods.